How do big data and data analytics impact the external audit ? A critical analysis - Heck, Natascha (Université de Liège, 2019)
The aim of this research is to determine how the application of Big Data and Data Analytics techniques influences the external audit. The impact on the working methods and the audit quality is discussed. Furthermore, the technological maturity of the Belgian and Luxembourgish audit industry is analysed. Therefore, the following research questions are asked: How do Big Data and Data Analytics influence the audit working method? What is the impact of Big Data and Data Analytics on the audit quality? How is the audit risk identification and assessment phase influenced? Which audit risks can be identified? Which tools and techniques do the Belgian and Luxembourgish auditors use and where do they stand? In order to answer the research question, scientific articles were analysed in the context of the literature review. Subsequently, a case study was carried out. Interviews with experts in Belgium and Luxembourg were conducted. The results of the research show that there is high potential to use these technologies in audit. Nevertheless, it is also connected with initial investments and a certain agreement of the clients. There is high potential to enhance the auditor’s effectiveness and efficiency, but the complete impact cannot yet be analysed. The audit quality can be enhanced when qualitative analyses generates audit evidence based on high quality data. The Belgian and Luxembourgish audit industry has just started implementing the technologies.
Keywords: Audit; Big Data; Data Analytics; External Audit

The power of will and choice of law in international contracts - Dazzi, Pietro Giulio (LUISS Guido Carli, 2019)
Party autonomy and sovereignty. Historical developments on party autonomy, the evolution of choice of law. The freedom of choice. The freedom not to choose, absence of choice. Limits to the freedom of choice. Limits to the freedom of choice, an expression of sovereignty. Same functions, different results.

A critical analysis of the effectiveness of the business rescue regime as a mechanism for corporate rescue - Bagwandeen, Kiren Kesh (University of KwaZulu-Natal, 2019)
Almost eight years after the enactment of the business rescue regime under the Companies Act 71 of 2008, and a plethora of judgments which have probed and prodded its provisions, it is an opportune time to ascertain whether the business rescue regime is an effective corporate rescue mechanism suitable to the modern day demands of the South African economy. In the current economic downturn, South Africa can ill afford a repeat show of the failed judicial management system. It requires a modern and effective corporate rescue mechanism that can be utilised in appropriate circumstances as a viable alternative and not merely a precursor to liquidation. This dissertation seeks to provide a critical analysis of the effectiveness of the business rescue regime to ascertain its worthiness as a corporate rescue mechanism.
Keywords: Bankruptcy; Business failures; Corporation law; Insolvency; South Africa

A Comparative Study of ECOWAS and ECCAS towards Implementation of the Abuja Treaty - Nyasembi, Kevin Selassie (University Of Ghana, 2019)
The Abuja Treaty is the blueprint and reference point for continental-level economic integration that was first established in 1991 to see to the creation of an African Economic Community (AEC). The Treaty acknowledges that, the African continent, as a unified unit of countries, wields immense power in the international system, in terms of trade and political influence, and thus it seeks to bring to fruition a highly integrated Africa. This study strives to evaluate the progress made on the implementation of the Treaty Establishing the African Economic Community (AEC) by comparing two regional blocs, the Economic Community of Central African States (ECCAS) and the Economic Community of West African States (ECOWAS), which serve as 2 of 8 building blocks for the realisation of the AEC. Accordingly, the research method used was qualitative and employed a purposive sampling method that draws on the selection of experts in the field of regional integration to shape the outcome of the study. The research findings include the fact that regional integration, on the continent, has progressed positively although it manifests slowly. Additionally, it found that both the ECOWAS and the ECCAS have progressed in terms of the implementation of the stages of the Abuja Treaty, although the former surpasses the latter in this regard. Yet, in spite of their progress, both RECs have faced challenges unique to their regions. ECOWAS for instance faces the problem of inability to completely enforce protocols on free movement of persons. The lack of national implementation of free movement legislation creates avenues for its ineffectiveness. Border checks are commonplace and there is very little standardization of official forms. ECCAS on the other hand faces a problem of overlapping goals and ideas with CEMAC as well as the failure of member states to carry out agreed decisions within their states due to issues such as conflict and instability in the region. On a whole, the study refutes the common idea that the Abuja Treaty has not been implemented at all but only sees its implementation as slow-paced.

The models of attribution in the establishment of corporate liability revisited - Heese, Francisca Alida (Stellenbosch University, 2019)
The separate legal personality of a company is one of the cornerstones of modern corporate law. Nevertheless, due to the artificial nature of a company it has no inherent moral blameworthiness necessary to impose corporate liability. With a rise in corporate wrongdoing, there is a need to hold companies liable. Therefore, certain models of attribution have developed whereby the conduct and will of a corporate actor can be imputed to the company to establish corporate liability. Especially in the realm of corporate criminal liability, these models of attribution have played a pivotal role to establish corporate wrongdoing. The two broad theories underlying the models of attribution are the fiction and realist theories respectively. The directing minds doctrine or identification doctrine and the vicarious liability model are traditionally associated with the fiction theory, which is rooted in the abstract nature of a company. Whether the traditional models of attribution are suited for complex modern organisational structures, is explored in this thesis, whilst a more functional and realistic approach to corporate liability is proposed. Often the question of “what is a corporation” has overshadowed the determination of corporate liability, thus a more contextual analysis based on law and economics is proposed to ensure corporate liability. The development of the rules of attribution through case law illustrate the importance of a purposive approach to establishing corporate liability. Furthermore, the underlying relationship between the rules of attribution and the rules of agency indicate that the interests of risk-bearers and managers are not always aligned and should be redressed. Moreover, a realist approach as opposed to the fictional approach to attribution has been developed in English and Australian law. This approach focuses on the overarching corporate culture and identity when determining corporate fault, instead of individual corporate actors. These regulatory frameworks provide an alternative approach to the current South African model, which is based on the fiction theory. Lastly, the economic considerations, such as the separation of ownership and control and the agency problem, are evaluated to determine whether the current models of attribution create an economically efficient outcome or an unsustainable a risk-taking environment.
Keywords: Corporate culture; Corporate liability; Corporation law

Choice of law in International Commercial contracts in the BRICS countries - Agbeko, Fafa Delight (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (International Commercial Law)

Rethinking international employment contracts in the wake of the Fourth Industrial Revolution - Antwi-Larbi, Nana Amobea (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (International Commercial Law)

Choice of forum in International Commercial Contracts : a comparison of the position in Ghana and under the Brussels IBIS regulation - Asante-Aboagye, Benedicta (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (International Commercial Law)
Keywords: Belgium; Border trade; Conflict of laws; Ghana; International commercial contracts; Litigation

The treatment and recognition of company groups in South African corporate law - Diale-Ali, Regomoditswe Ursula (University of Johannesburg, 2019)
Abstract : Please refer to full text to view abstract. LL.M. (Commercial Law)

A critical appraisal of call centre contracts for insurance - Dladla, Mbongeni George (University of Johannesburg, 2019)
Abstract : Please refer to full text to view abstract. LL.M. (Commercial Law)

The release of liability of a surety during business rescue proceedings - Dubula, Mcebisi (University of KwaZulu-Natal, 2019)
Chapter 6 of the companies Act has attempted to resolve problems created by the ineffectiveness of judicial management which has failed to provide suitable alternative to the liquidation. The process of business rescue proceedings has made some impact on the liability of sureties in so far as it relates to creditors. Moratorium has been imposed once the business rescue proceedings commences and therefore the principal debtors are protected against any legal action unless the court or business rescue practitioner has consented thereto. The question is what is the impact of the business rescue proceedings on the rights of creditors against the sureties of the company under business rescue proceedings and what is the judicial position in so far as it relates to liabilities of sureties during business rescue proceedings, finally what is the position of comparative law in respect of other foreign Jurisprudence terms of business rescue proceedings and the liability of sureties. The South African Companies Act does not regulate the situation of creditor’s rights against sureties of a financially distressed Company. In terms of American law, the situation is different. Creditor’s rights against non-debtors (including sureties) is regulated by Bankruptcy Codes. In terms of bankruptcy codes, the discharge of a debtor does not affect the liability of the nondebtors or other entities. There are divergent views in terms of South African Court decisions in respect of liability of sureties. Some Judges believe that the commencement of business rescue proceedings does not affect the liability of sureties and others are of the view that the beginning of business rescue proceedings releases sureties from their obligations towards creditors unless business rescue plan or deed of suretyship provides otherwise. It is therefore recommended that our legislature introduces some new sections into the companies act. One Section should be similar to section 524(e) of the bankruptcy codes which expressly states that a discharge granted to the principal debtor does not affect the liability of sureties towards creditors. Another section should be similar to section 105(a), which provide courts with powers to make any order to realize the objectives of the companies act. This to avoid conflicting courts decisions on this issue.
Keywords: Bankruptcy; Creditors' rights; Insolvency; Liability of sureties; Reorganisation process; Suretyship

The role of the Hague principles on choice of law in international commercial contracts in Japanese private international law - Geraghty, Brandon Brian (University of Johannesburg, 2019)
Please refer to full text to view abstract LL.M. (International Commercial Law)
Keywords: Conflict of laws; Contracts (International law); Japan

A comparative analysis of mergers and acquisitions in South Africa, Botswana and Kenya : how can we achieve successful integration in Africa? - Gumede, Nomfundo Pretty (University of KwaZulu-Natal, 2019)
No abstract available.
Keywords: Acquisitions; Amalgamation; Bots; Business; Corporate mergers; Integration; Kenya; Mergers; South Africa

The contractual landscape and the protection of consumers in online auction contracts - Khan, Haleema (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (Commercial Law)

Aquilian liability : the best remedy against delinquent company directors - Kharametsane, Godirilwe (University of Johannesburg, 2019)
Abstract : Please refer to full text to view abstract. LL.M. (Commercial Law)

An analysis of reinstatement as a primary remedy for unfair dismissal of employees in South African Labour Law - Mampholo, Yvonne Mokhubane (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (Commercial Law)

Intermediaries and advisors' duties to disclose onerous clauses to prospective policyholders - Matshitse, Collen Kgaolo Stephen (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (Commercial Law)
Keywords: Commercial law; Insurance law

The recovery of cultural property in international law: collaborative settlements of disputes - Mauro, Benedetta (LUISS Guido Carli, 2019)

An investigation into the effectiveness of trade unions in advancing the cause of workers during strikes in the face of an emerging culture of violence and criminality - Mfusi, Pearl Dawn Arnold (University of KwaZulu-Natal, 2019)
No abstract available.
Keywords: Labour protests; Liability; Strikes; Trade unions; Violent protests; Violent strikes; Workers

Towards development-centred trade relations: a study of South Africa and the USA trade relations with particular focus on the African Growth and Opportunity Act (AGOA) - Mkhwanazi, Nhlakanipho (University of KwaZulu-Natal, 2019)
With trade taking place continuously on a daily basis, its often-reported success gives the impression that all participants involved are to a certain extent somewhat successful too. This dissertation draws attention to the discrepancies that have often gone unnoticed throughout the decades and the effects that have arisen as a result. South Africa’s (SA) and the United States of America’s (US) trade relationship through the African Growth and Opportunity Act (AGOA) is the focus of this study, with this relationship being analysed from as far back as history has been recorded to the modern day. Least developed countries (LDCs) are an integral part of this study because most trade-related activities involve them, and they contain most of the world’s natural resources, but most importantly they also make up a large portion of the world’s population. It's baffling to see that where these factors are present, there's also inequality. Seemingly, there are efforts that deal specifically with the challenges faced by developing countries, but what is concerning is these solutions are formulated by developed countries which created them and continue to perpetuate them. The approach adopted was mostly that of contrasting events that have involved trade over the decades and a discussion of how these events have shaped international, political and trade relations, that is, the existing status quo. Examples include the two World Wars; oppressive regimes such as apartheid; and the formation of global institutions ranging from the International Trade Organization (ITO) to the General Agreement on Tariffs and Trade (GATT), and the World Trade Organization (WTO). The first three chapters contain an introduction, a background focus on development and the history of relations between South Africa and the United States of America. The last two chapters contain a discussion on AGOA as well as findings and recommendations that can be implemented to assist with this issue. What this dissertation was aiming to establish was the perpetual involvement of developed countries in the affairs of developing countries. This is illustrated through the renegotiation of the AGOA in 2015, where SA had to accept ultimatums set for it by the US. This dissertation further shows that such tactics are nothing new when the US is involved, as is evidenced by its involvement in major global events that have shaped the course of history. This approach is not only harmful but also stagnates development, as developing countries must adhere to agreements that sometimes are not to their benefit. The findings indicate a contradictory pattern: when solutions to challenges faced by developing countries are presented, they translate instead into a further stronghold over developing countries because of past atrocities such as colonisation and apartheid. What appears throughout the dissertation are the ever-present structures that are intended to perform functions supposed to be for the improved good of developing countries, but which result in those countries facing never-ending challenges, some of which are self-inflicted through alliances such as the AGOA with developed countries.
Keywords: AGOA; African Growth and Opportunity Act; Developing countries; Dumping; GATT; General Agreement on Tariffs and Trade; Trade relations; WTO; World Trade Organization

Price reduction as a remedy for breach of contract by the seller under the CISG and English law - Mukuna, Nomator (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (Commercial Law)

The interruption of liquidation by business rescue application: a lacuna in the Companies Act - Ntingane, Neo Samantha (University of Johannesburg, 2019)
Abstract : Please refer to full text to view abstract. LL.M. (Commercial Law)

The rights of illegal workers not to be unfairly dismissed, with emphasis on illegal immigrants and sex workers - Ntshalintshali, Phindile Ziningi Glenn (University of KwaZulu-Natal, 2019)
Illegal workers have been and continue to be the most vulnerable category of employees in the labour market, the reason for this is the invalidity of their employment contract due to illegality. For the longest time, the Labour Relations Act (hereinafter the LRA) has not been able to afford these workers protection because they did not fall within the ambit of the legal definition of ‘employee’ and the Act only recognises employees as holders of the rights provided for under the LRA. As a result of the Act not being able to protect these workers, they have become victims of exploitation and vicious abuse in the hands of their employers, making them vulnerable in their employment relationship. The law concerning illegal workers has since changed. Courts have found that these workers are in fact employees for the purposes of the LRA, and that, for an employment relationship to exist there need not be a valid employment contract in existence. An employment relationship may take various forms and the goal that the Labour Relations Act seeks to achieve is to protect those employees who find themselves vulnerable as a result of the illegality of their employment contract. It has also been argued that the law aims mostly at penalising the employer rather than the employee who is economically and socially weaker than the employer, therefore, courts have found that the Labour Relations Act should be interpreted in a manner that is consistent with the Constitution of the Republic of South Africa (hereinafter the Constitution) which requires a wider interpretation of who may be afforded the right to fair labour practices.
Keywords: Illegal workers; Immigrants; Sex Workers; Unfair dismissal

The rights and duties of parties to liability insurance contracts at claim stage - Ntuli, Bonginkosi (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (Commercial Law)
Keywords: Insurance claims; Insurance policies

Business rescue: a delay tactic for liquidation? - Nxumalo, Misiwe Mpilenhle (University of KwaZulu-Natal, 2019)
No abstract provided.
Keywords: Business rescue; Company creditors; Company law; Liquidation; Shareholders

The possible impact of the Hague Convention on the recognition and enforcement of foreign judgments in civil or commercial matters on private international law in common-law West Africa - Okorley, Solomon (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (International Commercial Law)

The position of a director in South African Law : is it worth the risk - Raselo, Moeketsi Thebe (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (Commercial Law)

Exemption clauses : contractual exclusion of delictual damages - Sande, Janet (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (Commercial Law)

Unification of international sales law in the SADC region : the role and significance of the CISG - Simelane, Mbalenhle Pearl (University of Johannesburg, 2019)
The United Nations Commission on International Trade Law (UNCITRAL) is one of the most prominent legal bodies in international commerce. In 1980, the final draft of the United Nations Convention on Contracts for the International Sale of Goods (CISG or the Convention) was approved by the United Nations (UN) General Assembly and came into operation on 1 January 1988. Generally, the diversity of laws is an impediment to international and regional trade. Traders are discouraged from entering into international sales contracts due to the dissimilarities of legal systems. However, the CISG seeks to unify laws relating to the international sale of goods, whilst codifying the existing rules of international trade. The main objectives of the Southern African Development Community (SADC) are to achieve development and economic growth through regional integration.1 The legal integration and unification of sales law has a significant role to play in regional integration. Hence, SADC would do away with difficulties that affect interregional and intra-regional trade by impeding economic growth by making use of widely accepted trade laws, such as the Convention. International trade promotes both economic development and social upliftment. Moreover, democracy, political stability and human rights must be respected to foster sustainable economic growth and development in Southern Africa. 2 With advantages such as accessibility, flexibility, indorsing party autonomy, simplicity, and uniform interpretation, the paper revisits the call for the unification of laws on the sale of goods in SADC and considers the role and significance of the CISG in the region. LL.M. (Commercial Law)
Keywords: Commercial law; International economic integration; International trade Law; International unification

An appraisal of the implementation of the retail distribution review's recommendations - Wilkins, Chanel (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (Commercial Law)

Determining the proper law of an International Funds Transfer - Yeboah, Abena Takyiwa (University of Johannesburg, 2019)
There are many ways of making payments. One of the available options for parties to international commercial transactions is international funds transfers. These transfers occur across borders and so, raise conflict of law issues. There are some laws known internationally that regulate international funds transfers. These laws include the UNCITRAL Model Law on International Credit Transfers (no country has ratified it), article 4A of the Uniform Commercial Code and the Rome I Regulation. There are diverse ways in determining which law applies to an international funds transfer. This is done either by assessing the transaction as a single transfer or as a set of linked transactions. In African countries like Ghana and South Africa, there is a gap in the approach of the law in addressing the conflict of laws issues regarding international funds transfers. This dissertation addresses the gap in these legal regimes using the present private international law as a guide. Additionally, the present legislation and legal jurisprudence are analysed, and suggestions are given as to its improvement. This author also advocates for a legislation that adequately addresses the issues raised by transnational funds transfers in these countries. Conclusively, this will promote a predictable approach in determining the applicable law in transnational funds transfers.
Keywords: Fund transfer; Transfert de fonds; Transfert international

The role of the SADC Protocol on Trade in Services in regional integration - Swanepoel, L. B. (North-West University, 2018)
Trade in Services can be described as a transaction between a supplier and a consumer without any physical movement of goods across international borders. This, in itself, presents major economic growth possibilities in both regional and multilateral terms. Regional trade agreements, if drafted to suit the specific region's strengths, can promote Trade in Services and establish regional integration. The fact that Trade in Services and regional integration, throughout the Southern African Development Community (SADC) specifically, is moving forward at such a slow pace is due to the lack of political ambition and policy makers failing to emphasise the establishment of trade specific regulatory coherence among member states. Given policy’s impact on Trade in Services, regional trade agreements must be designed to address new and emerging issues that, not only haven't been taken up in previous trade agreements, but which is also region specific and focused enough to build on new standards found in other new trade agreements that will boost regional integration. SADC countries are still in process of establishing a regional services market and, as it currently stands, major development possibilities still exist. This study compares the Trans-Pacific Partnership (TPP) with SADC’s Protocol on Trade in Services (PTIS), with the goal to determine the principles that are necessary to establish a regional market for the integration of Trade in Services. It was found that the PTIS lacks such principles and that integration of services throughout the SADC region is highly unlikely if set forth in its current direction. The finding was that the establishment of regional integration of Trade in Services throughout SADC will have to start with regulatory coherence among its members.
Boloka Institutional Repository https://repository.nwu.ac.za/handle/10394/31341
Keywords: Modes of trade; Regional integration; Regulatory coherence; Trade in Services

Trade Openness and Financial Development in Sub Saharan Africa: The Role of Institutional Quality - Abeka, Mac Junior (University of Cape Coast, 2018)
The financial development of many Sub-Saharan African countries over the years has not been able to match up with other regions like the Middle East and North Africa, East Asia and Pacific, and Europe and central Asia (IMF, 2016). Trade openness has been argued in several empirical literature as a factor that could spur up the level of financial development, although the high levels of trade openness in Sub-Saharan Africa is not contributing much to the desired levels of financial development in Sub-Saharan Africa. However, there is an indication in literature that trade openness will be more relevant to financial development of economies that have a strong institutional quality. Thus, by using system General Method of Moment estimation technique, this study examined how institutional quality moderates the relationship between trade openness and financial development of Sub-Saharan African economies. The study found that institutional quality enhances the effect of trade openness on financial development of Sub-Saharan African economies. It is therefore recommended that, Sub-Saharan African economies should put in measures to strength their institutional quality so that the high levels of trade openness will better enhance financial development. Specifically, trade openness can better enhance financial development by improving government effectiveness, reducing corruption, enhancing regulatory quality, abiding by the rule of law, and allowing voice and accountability. As an extra benefit, the improvements in institutional quality on their own too will yield positive impact on financial development.
http://ir.ucc.edu.gh/jspui/handle/123456789/4084

Cross border merger and shareholder's rights - Severino, Francesco (LUISS Guido Carli, 2018)
Historical context. Scope of application of cross border merger. A comparison of class rights with minority protection in cross border merger. The transposition of the cross border merger in the German law for an implementation.

An analysis of the effects of tax policy and tax abuse on the fulfilment of human rights in developing countries : the case of Zambia - Chigubu, Salome (University of Johannesburg, 2018)
Keywords: Droit fiscal; Pays en voie de développement; Politique fiscale; Tax; Zambie

The position of assets vested in a sham trust - Diedericks, C. A. (North-West University, 2018)
The concept of a sham trust has changed over the years. Presently it is defined as a perceived entity that is not entirely what it portrays to be. In addition, a sham is therefore regarded as invalid with a deceiving nature. A sham trust has the consequence that all the benefits and protection of assets are destroyed, seeing that no trust actually came into existence. Considering the above, for the purpose of the present study, only an inter vivos trust was evaluated and discussed in detail. The law of contract is considered to be the foundation of the principles for an inter vivos trust. Therefore, the law of contracts can be applied to solve problems presented by trusts. During the course of the present research, it became evident: in instances where a trust is declared a sham, the consequence is that the trust will be deemed void. There are instances where a sale agreement has been concluded prior to the discovery of the true nature of the trust, namely it being a sham. This raises the question on the legal position of assets vested in a sham trust. A further question arises about the consequences and whether the courts should set a guideline for such instances. From the findings it is evident that such a guideline is necessary. This would enable courts to determine the consequences of assets vested in a sham trust. There are various possibilities regarding consequences for assets vested in a sham trust. To determine the applicable consequence, the court should deal with each case individually based on the facts of that particular circumstances. This consequence could either entail that the assets should fall within the founder’s personal estate, or whether the concluded sale agreement should be deemed void. It is evident that the courts struggled with the distinction between a sham and alter ego trust, however, the case law referred to below gives more clarity in this regard. A proper formulation of the aspects of sham and alter ego trusts was provided in the cases of Van Zyl v Kaye1 and Van der Merwe v Hydraulics.2 The formulation of the two aspects in the above-mentioned cases was confirmed in the Supreme Court of Appeal judgement in the case of WT v KT.3 In the Khabola v Ralitabo,4 the court dealt with the typical example of the sham trust. In brief, the fact of the case were, that the parties had the intention to establish a partnership that was simulated to be a trust.
Boloka Institutional Repository https://repository.nwu.ac.za/handle/10394/31321
Keywords: Assets; Contract of sale; Intention; Law of contract; Legal position; Sham trust; Snook test; inter vivos trust

A comparative analysis of constructive dismissal in South Africa and within other international jurisdictions - Kader, Riaz (University of KwaZulu-Natal, 2018)
Abstract available in PDF.
Keywords: Constructive dismissal; Employee termination; Employees; Employers; Employment relationship; Termination of employment

Choice of law in international commercial contracts : a comparative study of Private International Law in Ghana and South Africa - Kwame, Essah (University of Johannesburg, 2018)

A comparative legal perspective on the impact of good or bad faith on the independence of documentary credits and demand guarantees - Lupton, Cayle Selwyn (University of Johannesburg, 2018)
Abstract : Please refer to full text to view abstract. LL.M. (Commercial Law)

Modification of choice of law in the BRICS countries : the role of Article 2(3) of the Hague Principles on choice of law in international commercial contracts - Ndlovu, Docus Sanele (University of Johannesburg, 2018)
Each member state of the BRICS countries is different about the modalities and limitations of party autonomy in their field of Private International law. The principle of party autonomy allows parties to choose the law applicable to their contract and is meant to respect the choice of contracting parties. Since laws are not absolute, they need to change to the needs of a changing society. This can generate a problem in instances where contracting parties have already chosen a choice of law to govern their contract. The question is then whether the governing law of a contract that was previously chosen by the parties can be changed after that contract has been concluded. The scope of party autonomy extends to permitting parties to modify their chosen law in instances where it is necessary to do so, subject to limitations of a specific legal system and principles of conflict of laws. However, the legal rules of each BRICS countries differ in permitting parties to modify the chosen law. This minor dissertation analyses whether the principle of party autonomy is recognised in each member state of the BRICS countries and whether it extends to allow for modification of choice of law. It further asserts that the BRICS countries could plausibly refer to the rules and recommendations of Article 2(3) of the Hague Principles on Choice of Law in International Commercial Contracts to advance the wide acceptance of modification of choice of law. LL.M. (International Commercial Law)

The directors’ fiduciary duty to act in the best interests of the company: the possible developments of common law by statute and how they affect human rights - Nomadwayi, Bakhulule (University of KwaZulu-Natal, 2018)
This research traces the developments of the directors’ fiduciary duty to act in the best interests of the company and looks at how these developments affect human rights and interests of stakeholders. The main focus of the study is on the human rights impact of this duty. Initially, this duty was only regulated in terms of common law which proved to be problematic. The problem with common law lies within the definition of ‘best interests of the company’, which not only exclude the interests of other stakeholders but also has the potential to bring about violation of human rights, particularly the rights to equality, dignity and fair labour practice. At common law best interests of the company means interests of the company itself and its shareholders. The common law only protects the company and its shareholders, while excluding the rights and interests of stakeholders. The common law duty to in the best interests of the company is not in line with our contemporary law because it ignores human rights. The neglect of human rights by this duty renders it inconsistent with the values contained in the Constitution. Furthermore, the exclusion of stakeholders’ rights by this duty cannot be justified because stakeholders play an important part in safeguarding the stability and continued existence of the companies. The fiduciary duty to act in company’s best interests is now contained in the Companies Act of 2008. Inclusion of this duty in the Act enables our courts to interpret it in a manner that protects human rights and which takes into account interests of other stakeholders. Section 7 (a) of the Act provides that among other goals of the Act is the promotion of compliance with the Bill of Rights when applying the company law. The impact of section 7 is that it imposes an indirect duty on directors to consider the human rights impact of their decisions. Section 158 of the Act enables the courts to “develop common law as it is necessary to improve the realisation and enjoyment of rights established by the Companies Act of 2008.” Given this recognition of the Bill of Rights by the Companies Act, it’s of vital importance that our courts should interpret and apply the duty to act in the best interests of the company in manner that is consistent with the Constitution. Directors are now obliged to pay attention to the human rights impact of their decisions.
Keywords: Best interests of the company; CSR; Corporate Social Responsibility; Fiduciary duty

Reckless and fraudulent trading by a company and the business judgment rule as a defence for directors - Peter, Lunga Cosmo (University of KwaZulu-Natal, 2018)
Abstract available in pdf.
Keywords: Business judgment rule; Company directors; Corporate governance; Fiduciary duties; Fraudulent trading; Good faith; Personal liability

Analysing and comparing the impact of misrepresentation and non-disclosure on the validity of a contract: similarities, differences and remedies - Ramphal, Kayra (University of KwaZulu-Natal, 2018)
This dissertation explores the concepts of non-disclosure and misrepresentation in South African law. The principal focus surrounds the effect non-disclosure as a form of misrepresentation has on the liability of contracting parties. In order to explore this effectively, the study explores the concept of duty of disclosure, and whether such a duty exists in South African law. Instances when a duty to disclose arises are explained, such as positive steps taken to conceal facts, the seller having sole knowledge of the material fact, an omission or misleading language, and a change in circumstances. Similarly to the English law duty of disclosure in relation to information in contracts uberrimae fidei, the similar South African law concept in insurance or agency contracts known as ‘utmost good faith’, is discussed and explored. The study determines whether such a concept should be a mandatory requirement in pre-contractual negotiations. Additionally, this study explores the various avenues of relief that are available to those who have fallen victim to misrepresentation. This results in an analysis of the effectiveness and success of the current traditional methods of claiming and quantifying damages that are adopted by South African legislature and the judiciary. The discussion then explores the proposed alternate method which aims to combine a claim into one of delict and that of contractual liability, or on the other hand institute a claim solely based on contractual liability. Lastly, this study explores the effect the Consumer Protection Act 68 of 2008 has had on contractual agreements, remedies and penalties, and how this ground-breaking legislation has altered the approach previously adopted by the common law and whether it has done enough to protect consumers.
Keywords: Contracting parties; Contracts; Duty to disclose; Liability; Misrepresentation; Non-disclosure

The interconnection between express choice of forum and tacit choice of law. A comparative analysis between common-law and civil-law jurisdictions - Roux, Keegan (University of Johannesburg, 2018)
Keywords: Commercial law; Conflict of laws; Contracts (International law)

The link between reckless credit and emolument attachment orders - Singh, Nishtha (University of KwaZulu-Natal, 2018)
South Africa has experienced significant levels of reckless credit thus leading to over-indebtedness of consumers. Furthermore, research conducted in 2008 and 2013 by the University of Pretoria indicated that there were abuses prevalent in emolument attachment orders (EAOs). An interesting aspect of the research was that credit providers were particularly interested in employed consumers, as their wages or salaries were deemed to be a form of security. The aim of this dissertation is to examine the link between reckless credit and EAOs. The main research problem revolves around the fact that credit providers do not conduct thorough pre-agreement assessments and have a tendency to subscribe to the tick box approach to compliance. Moreover, these pre-agreement assessments do not make provision for the inclusion of external market factors, which is essential to safeguard consumers against economic events. This dissertation argues that, at the point when reckless credit is granted, it is inevitable that default will occur thus leading to the culmination of an EAO. In this regard, the case of University of Stellenbosch Legal Aid Clinic and Others v Minister of Justice and Correctional Services and Others; Association of Debt Recovery Agents NPC v University of Stellenbosch Legal Aid Clinic and Others; Mavava Trading 279 (Pty) Ltd and Others v University of Stellenbosch Legal Aid Clinic and Others (CCT127/15) [2016] ZACC 32 is important. The judgement illustrates how vulnerable consumers fell prey to unscrupulous credit providers who then took advantage of their salaries. An important aspect about the judgement was that section 65J of the Magistrates Court Act has now been amended through a joint interpretative mechanism of severance and reading in. The Constitutional Court’s order now requires judicial supervision in the EAO process, whereby a magistrate issues the EAO. This dissertation examines the effect of this and how EAOs are currently regulated. It also discusses whether judicial supervision is the solution to ameliorating the law on EAOs. Qualitative research methods were utilised such as legislation, case law, textbooks and journal articles. While there are no statistics to prove the link, anecdotal evidence proves the link between reckless credit and EAOs.
Keywords: Credit market; Emolument Attachment Orders; Protection of Personal Information Act; Reckless Credit

Restraint of trade clauses: does the enforcement thereof promote anti-competitive behaviour in South African law? - Sithole, Mthokozisi Wesley Nhlakanipho (University of KwaZulu-Natal, 2018)
No abstract available.
Keywords: Anti-competitive behaviour; Business agreements; Competencia; Competition law; Employment agreements; Restraint of trade; Trade clause

A discussion of the success and failures of business rescue as a remedy for ailing companies - Sobantu, Vuyo (University of KwaZulu-Natal, 2018)
Companies are constantly facing risks, including financial constraints, which may contribute to companies being unable to trade in the manner desired. Unfortunately, companies that find themselves in this predicament have, in reality, been without a remedy from as early as statutory provisions regulating company law were promulgated in 1926. Judicial management, as a remedy, is notorious for being an outright failure, but the current Companies Act 71 of 2008 introduced the remedy of business rescue for financially distressed companies. The scrutiny and spotlight on the new remedy turns on whether it can be truly accessible for the companies in question and what significant changes it has made to favour financially distressed companies. This mini dissertation will aim to discuss whether the remedy of business rescue has been a success or failure.
Keywords: Ailing companies; Business rescue; Companies Act 61 of 1973; Companies Act 71 of 2008; Judicial management; South African company law; Winding up

A critical analysis on simulated transactions - Tshabalala, Alwanduxolo Thembalihle (University of KwaZulu-Natal, 2018)
No abstract provided.
Keywords: Simulated transactions; Tax avoidance; Tax evasion; Taxation

The effects of business rescue on the companies’ stakeholders : a comparative analysis between business rescue and judicial management - Xaba, Ntombikhona Thandeka (University of KwaZulu-Natal, 2018)
Upon the recognition that the implementation of the judicial management process would not be the success that it was anticipated it would be, it became apparent that there was need for a system of corporate rescue appropriate to the needs of a modern South African economy. The legislature then introduced a new business rescue regime when the Companies Act 71 of 20082 (the Act) came into effect in the South African law. This new Act remarkably changed corporate law. One of the central features of the Act is the introduction of business rescue- a procedure which provides for the rehabilitation of financially distressed companies in a manner that seeks to balance the rights of all stakeholders. These provisions are said to be the appropriate method for modern South African economy and they differently affect the stakeholders of a company. This thesis will be discussing the different rights given to affected persons in the new Companies Act and examine how the provisions of business rescue affect different stakeholders of the company and compare such effects with those experienced under judicial management, specifically in light of the improvements of the positions of the stakeholders. Although the new business rescue is a remarkable improvement from the old judicial management system, there is still room for improvement.
Keywords: Business rescue; Companies Act 71 of 2008; Company stakeholders; Judicial management; South African company law

A critical discussion of the directors’ duties and business judgement rule - Zondi, Sphesihle Brilliant (University of KwaZulu-Natal, 2018)
No abstract available.
Keywords: Companies Act 71 of 2008; Directors; Judgement rule; South Africa

Treatment of corporate groups in insolvency under EU law - Sicignano, Luca (LUISS Guido Carli, 2017)
L’analisi svolta in questo lavoro ha ad oggetto le procedure adottabili in caso di fallimento, quando esse coinvolgono società costituite in gruppi di impresa. È una questione non recente che ha tuttavia avuto la sua consacrazione nel panorama internazionale solo negli ultimi anni. La grande crisi finanziaria del 2008 ha fatto sorgere la necessità di emanare nuove specifiche regole. Pertanto, l’obiettivo che questo lavoro si propone, è di analizzare tali regole, sia iure condito che iure condendo, per consentire al lettore di avere una panoramica chiara su come l’insolvenza di gruppo possa essere trattata.

Dissenting Opinions in International Commercial Arbitrations - Mohanty, Gautam (Central European University, 2017)
A dissenting opinion with reference to International Commercial Arbitrations elementarily denotes the expression of disagreement by an Arbitrator in relation to both the reasoning and the result of the award granted by the majority of the Tribunal. Though still at a nascent stage, the practice of delivering dissenting opinions is one which needs to be duly noted and taken into due consideration because of the incidental and collateral questions that it nurtures. Fundamentally, a dissenting opinion raises concerns related to the effect, the nature and the rectitude of such opinions. One such collateral question is the enforceability of such dissenting opinions and the repercussions that follow in the context of an arbitral award delivered by the majority. In addition to the above raised question, through this thesis the author will also address other questions such as whether the act of delivering a dissenting opinion is an indicator of the increased sense of maturity of arbitrators in international commercial arbitration? Whether the dissenting opinion possesses any precedential value to the arbitration cases arriving prospectively? and How do such opinions contribute to the development of arbitration jurisprudence. Moreover, through this thesis the author will also attempt from a comparative perspective to examine and make an incisive analysis of the governing rules of arbitration across various arbitration regimes such as ICSID, LCIA which already have a wellestablished arbitration jurisprudence.

An investigation into the relationship between the UNIDROIT Principles of International Commercial Contracts (UPICC) and the UN Convention on the International Sale of Goods (CISG) - Daniel, Jason (University of Johannesburg, 2017)
LL.M. (International Commercial Law) Please refer to full text to view abstract
Keywords: Commercial law; Conflict of laws; Contracts (International law); International Institute for the Unification of Private Law; UNIDROIT principles of international commercial contracts 2010; United Nations Convention on Contracts for the International Sale of Goods (1980 April 11)

Special and differential treatment provisions within the World Trade Organization : the pursuit of development for developing countries - Hiine, Karabo (University of KwaZulu-Natal, 2017)
Abstract not available.
Keywords: Differential Treatment Provisions; Multilateral system; Special Treatment Provisions; Trade liberalization; WTO; World Trade Organization

Alternative Dispute Resolution in Oil and Gas Contracts Law: An Analysis - Kareem, Kareem Kawa (Near East University, 2017)
The industry of oil and gas is not peculiar to question anymore, inferable from the global condition as well as its various dimensions. While trying to complete an agreement procedure, it would barely be clear to expect the thing that could happen in the emergence of a debate. Hazard moving and fragmented contracting lie at the heart of the organization relationship innate in the obtainment and financing of extensive scale undertakings, such as power plants, oil and gas pipelines, and condensed natural gas facilities. An examination of gas bonds gives exact proof of the hazard moving results of legally binding inadequacy. This thesis is a basic examination of the discipline we call the law of oil and gas. A number of the imperfections connected with this "specific" status. Jurisprudential with its "uncommon" status. Jurisprudential imperfections have created as courts leave from essential contract, property, or tort law in quest for natural resources ideas. The marvel isn’t restricted to natural resources law but instead can occur in any "law of" setting. This article delineates the issues connected with oil and gas law by dissecting legal ways to deal with perceiving and applying "inferred agreements" under the oil and gas rent. By contrasting the experience and results under the oil and gas lead to the result under an agreement law investigation, it is conceivable to assess whether a specific "oil and gas" govern is vital or prudent. In the past quarter-century, huge changes have happened in the ways legal advisors approach strife. There have been uncommon endeavors to create systems went for more proficient, not so much expensive, but rather more fulfilling determination of contention, including more broad and suitable utilization of intercession and other " alternative dispute resolution " (ADR) approaches. This review analyzes what is known and not considered about the development and effect of ADR in government and state courts, in the business division, and in work and shopper settings. The investigation inspects the relationship amongst ADR and court trial, additionally underlines the more extensive employments of and method of reasoning for intercession and different process decisions. This study concentrates on the oil and gas contract with question by ADR.

Recognition and enforcement of foreign judgments : proposals for OHADA - Kazadi, Nshingu (University of Johannesburg, 2017)
LL.M. (International Commercial Law) Please refer to full text to view abstract
University of Johannesburg Institutional Repository (UJ IR)

A critical analysis of the fiduciary duties of directors and evaluation of the development of these duties in terms of the common law and statutory law - Mdunge, Mzwendoda Smiso Patson (University of KwaZulu-Natal, 2017)
Corporate law is based on the premise that directors are fiduciaries of their companies. This is an unbending duty which has to be adhered to at all cost by individuals appointed as directors of a company. Previously the director’s duties were governed by the common law which often relied on the interpretation of the courts on a case by case basis. Therefore the courts would often arrive at different conclusions based on a similar set of facts. The advent of the 2008 Companies Act (Act 71 of 2008)1 brought about a major evolution in South African company law by partially codifying the fiduciary duties of the directors. Understanding fiduciary duties of a director is of significant importance in the modern democracy based on the fact that directors engage on the international spectrum. Company directors have discretionary power which may be abused if they are not familiar with the fiduciary duties. This study seeks to comprehend fully the fiduciary duties of a director of a company. These are the duty to act bona fide, the duty to act for a proper purpose, the duty to avoid conflicts of interest and the duty not to use a corporate opportunity and information for personal profit. This task will be undertaken both in terms of the common law as well as statute (Companies Act 2008 Act). The study will delineate the fundamental consequences of partial codification of these duties and set out the current legal position of the common law which operates in tandem with the statute. In addition, it will deal with whether the common law provisions are still applicable side by side with the statutes. The duties of a company director represent a subject that is not merely academic in nature, but one that is of vital importance in our ever changing commercial world. More and more people are appointed as company directors every day and often they do not know or understand the implications of what they have agreed to.
Keywords: Common law; Companies Act 71 of 2008; Corporate law; Duties of directors; Duty to act in good faith; Fiduciary duties

Contractual regulation : infusing the law of contract with constitutional values - Ndlebe, Zithulele Fikile (University of Johannesburg, 2017)
The Constitution of the Republic of South Africa is the supreme law in the land. Thus, all law is subject to the Constitution and this inevitably includes the law of contract. The South African law of contract has been inherited from common law, namely Roman–Dutch law and has been applicable in South Africa to date. The Constitution states that the common law should be developed when it is not in line with the provisions of the Constitution. The values underpinning the Constitution are human dignity equality and freedom and these values must therefore be reflected in contractual relations. The common law principle of pacta sunt servanda, which means that agreements must be kept, at times this principle yields unjust and unreasonable results. The strict adherence to pacta sunt servanda has led to difficulties. The unenforceability of these contract terms has been shown in reported case law to stem from standard term contracts, unequal bargaining power and from persons who contract out of necessity. This dissertation concludes that South African law of contract and the current legal treatment of balancing contract law with constitutional values is unsatisfactory. The Bill on the Control of Unreasonableness, Unconscionableness, or Oppressiveness in Contracts or Terms which was tabled in 1998 should be revised and legislated, so as to regulate contracts and infuse the law of contract with the constitutional values of human dignity, equality and freedom.

The impact of leadership styles on organizational performance - Nzimande, Sandile Jerome (University of KwaZulu-Natal, 2017)
Many contemporary private and public enterprises have been hit by scandals and underperformance which have been linked to organizational leadership. This study therefore sought to establish the impact of leadership styles on organizational performance. Leadership and organizational performance crises that have rocked institutions such as Eskom, the South African Broadcasting Corporation and the South African Airways, Steinhoff, Enron and others necessitated the study. The study focused on MBA year three students (class of 2017) at the University of KwaZulu-Natal. The assumption has been that since these are masters’ students, they have once been exposed to various leadership styles, some of them are leaders, all have studied leadership styles and therefore likely to understand how these styles impact on organizational performance. This is a quantitative study. The total population was 140 students of which a total of 100 were targeted. Simple random sampling was used. Most of the participants revealed that there is a significant link between leadership styles and organizational performance. They unanimously agreed that there is definitely a noteworthy relationship between leadership styles and the organizational performance. The respondents also revealed that transformational leadership style is the most complimentary leadership style to organizational performance followed by strategic and open leadership styles respectively. Participants agreed that toxic leadership style and autocratic leadership style are undermining the organizational performance. It is therefore recommended that organizations ensure continuous checks on leadership in order to ensure that available leadership can assist in the realization of organizational goals. In addition, it is also recommended for organizations to assess the "type" of a leader in terms of leadership styles before he/she is promoted to take leadership roles in the organization in order to make proper placements. This will allow the organization to assess whether that type of a leader is suitable for the organization. Future research is needed on how models can be developed on how to make proper placements to leadership levels/roles. Research should also focus on how leadership styles dovetail with other organizational efforts that are meant to boost organizational performance.
URI: https://researchspace.ukzn.ac.za/handle/10413/21460
Keywords: Leadership styles; Organizational performance; Private enterprises; Public enterprises

Strategies adopted by Commercial Banks in Kenya in Response to the Law Capping Interest Rates - Ragor, Rodgers Kiptoo (University of Nairobi, 2017)
The ability of an organization to adjust its operation in light of the evolving changes in their operating environment determines the sustainability of the business unit in both the short and long term. The objective of the study was to determine the response strategies adopted by Kenyan commercial banks in response to the interest capping laws. A descriptive cross-sectional design was used. The population of the study was 42 commercial banks operating in Kenya. Primary data was collected using a questionnaire that was both closed and open ended. Data was analysed using the descriptive statistics. The study found that banks have employed adaptation strategies through working with other partners in the banking sector to leverage their synergy and concentrate on areas that enhance competitive advantage. The research findings also reinforced the need for the banks to work together as a sector and attempt and change the laws that inhibit their operations through lobby groups in parliament and other forums. The study also show that there exists a link between firms‟ strategic activities and their strategic responses and therefore, bank managers should diversify their product range especially to the youth who are apt in using the mobile technology to access services and improve the bank level of efficiency and effectiveness in their operations. The study recommends that the commercial banks ought to conform to the regulations to attract customers while the Central Bank as a regulator should likewise be sensitive to the operating environment and should be flexible in setting the rules in order to attract investment and support the growth in the banking industry. The Interest capping law is still at its infancy stage in Kenya and thus there is room for further research as the full impact of the law is realized in the long term.

The compatability of the restatement second of the conflict of laws and South African private international law with Article 2(2) of the Hague Principles on Choice of Law in International Commercial Contracts - Seckel, Ashely Zwelinhle (University of Johannesburg, 2017)
Please refer to full text to view abstract. LL.M. (International Commercial Law)

State interference through domestic courts in international commercial arbitration - Badenhorst, Casper Hendrik Jacobus (University of Johannesburg, 2016)
Keywords: Arbitrage; Arbitragem; Arbitration; International and municipal law; International commercial arbitration

The Interface Between Competition Law and Intellectual Property Law in Kenya - Jerobon, Rotich Caroline (University of Nairobi, 2016)
The interaction between competition law and intellectual property law has often attracted divergent views from scholars and practitioners of each respective sphere of law. Whereas some argue that the two are in conflict with each other and cannot be reconciled. The aforementioned tension between competition law and intellectual property law has been traced to the objectives of each. On the one hand, intellectual property rights confer upon their owners an exclusive right to behave in a particular way while on the other hand competition law strives to keep markets open. Other scholars have argued that, in real sense and practice, the two are actually not in conflict but rather that they complement each other. The question then becomes, is there really an irreconcilable difference between the two areas of law? This paper seeks to establish how the two aspects of law interact and seeks to propose that there be created a balance to alleviate the perceived conflict between the two. This paper will identify the areas in which the balance can be struck. It will also seek to establish how the Kenyan legislative framework as well as the courts has dealt with the conflict. It will proceed from understanding the goals and objective of both intellectual property law and competition law. This will provide the backdrop against which the alleged conflict originates from. A comparative study with other developed jurisdictions will be undertaken so as to advise on the route that should be taken by Kenya on the interface and a conclusion drawn on how the two areas relate and recommendations drawn from the issues identified in the study made.
Keywords: Competencia; Competition law; Intellectual property

The resolution of jurisdictional conflicts under the common law and in the European Union - Mlambe, Richard Mike (University of Johannesburg, 2016)
The resolution of jurisdictional conflicts is one of the main functions of private international law. It provided rules to be applied when the courts of more than one country are seized of the same case in international litigation. In determining what that rule should be, regard must be had to the interest of all the relevant entities, namely, the parties to international cases and the courts dealing with such cases. The need to strike a balance is even more urgent in international commercial litigation where the outcome of the case normally has significant economic consequences. From this background, a study has been conducted of two major private international law regimes regarding their approaches to the resolution of jurisdictional conflicts, namely, the common‐law and the European Union (EU). This study is an inquiry into the suitability of each approach in the resolution of jurisdictional conflicts in international commercial cases. It is the view of the present author that each approach has advantages and disadvantages. The common‐law through the doctrine of forum non conveniens shows a greater ability to prevent forum shopping and to prevent injustices in specific cases. However, it is highly unpredictable. On the other hand, the EU approach through the lis pendens rule succeeds in ensuring predictability and certainty in the resolution of jurisdictional conflicts which is very crucial in international commercial litigation. However, its rigidity and inflexibility leads to the determination of international commercial cases by courts that are ill‐suited, thereby giving some room for forum shopping. It is therefore recommended that the two approaches should learn from each other so that their handling of international commercial cases is in line with the special nature of international commercial litigation. The common‐law approach should be made more predictable and the EU approach should allow the courts in the EU to determine which court is best suited to deal with an international commercial case.

The implications of Lagoon Beach Hotel (Pty) v Lehane 2016 (3) SA 143 (SCA) for the South African cross-border insolvency dispensation - Moolman, Shirande (University of Pretoria, 2016)
This mini-dissertation explores the implications of Lagoon Beach Hotel (Pty) Limited v Lehane 2016 (3) SA 143 (SCA) for the South African cross-border insolvency dispensation, as this case deals with the various problems that arise in cross-border insolvency. As a result of these problems and a certain amount of uncertainty when it comes to dealing with cross-border insolvency issues, many investors are reluctant to invest cross-border. This is due to the fact that multiple countries, each with their own laws concerning cross-border insolvency, are involved. Thankfully, the United Nations Commission on International Trade Law has provided a set of guidelines in this regard, namely the Model Law on Cross-Border Insolvency. Although South Africa has enacted the Cross-Border Insolvency Act 42 of 2000, and most of the provisions provided for in the Model law have been included in the legislation, the Act still remains inoperative. Throughout this dissertation the Lagoon Beach case will therefore be critically analysed. The analysis will start off with a discussion of the common law, as it is currently the legal position in South Africa. Thereafter a detailed analysis will be conducted of the various orders of court of the Lagoon Beach case and how the courts differed or agreed in their approach. Finally, the Lagoon Beach case will be discussed in light of the Act and the issues in the case will be solved hypothetically by applying the Act to the problems discussed throughout the dissertation.

The transfer of ownership of movables in the context of international contracts of sale with specific reference to reservation of title clauses : a comparative study - Neibecker, Nadine (University of Johannesburg, 2016)
Please refer to full text to view abstract LL.M. (International Commercial Law)

Designing justice: a critical analysis of intellectual property rights within the fashion industry - Parbhoo, Sade (University of KwaZulu-Natal, 2016)
Designers are those individuals within our society with a desire and drive to create. In general designers can be found in all facets of industry and good designers (and ultimately good designs) are the very backbone upon a successful business is built. Designers are required to marry practical knowledge with artistic ability and we are reliant on their skills and to turn abstract ideas into formal designs for everything from the groceries we purchase, the cars we drive and of course, the clothes we wear. Whilst there is no definitive delineation of what a fashion design is, generally fashion designs relate to the creation of designs that focus on clothing, apparel and accessories. The style and functionality of the end products rest firmly within particular time frames, economic and socio-cultural environments within which particular designers find themselves. Accordingly the fashion design industry is never one that stagnates but rather is one that is constantly evolving. In South Africa, the fashion industry is blossoming. As an emerging economy, it is important to create opportunities and not barriers for entry into particular sectors for emerging entrepreneurs. The entire fabric of the fashion industry has certainly changed over time and these changes have brought an increased focus on issues of copying and counterfeiting. It is the contention of some in the industry that there is a need for stricter protection of the actual design in and of itself. Using intellectual property rights as a means of protecting fashion designs is very fitting as every new design begins with an idea, which then evolves, though a process of creative engagement and application of skill and labour to become the final original end product. Designers seeking to protect their designs would need to consider the provisions of the Copyright Act, the Designs Act and the Trade Marks Act. These Acts may in some instances provide a means for protect the actual design incidentally, i.e. by protecting the designer‟s rights in relation to reputation and goodwill associated with the goods whilst in others may afford protection to the design itself. The focus of this research will be a discussion of the legal mechanisms available to fashion designers in South Africa for the protection of their designs using their intellectual property rights and an assessment of whether the fashion industry is in need a stronger intellectual property regime than the current one.
Keywords: Design protection; Fashion industry; Intellectual property; Ownership; Retail trade; South Africa

Formation of Contract for the International Sales of Goods - Saleem, Saman Othman (Near East University, 2016)
The Convention for the International Sale of Goods called the Vienna Conference 1980 is an astute international statute that regulates the sale of goods globally. It has been ratified by about 83 countries of the world and countries that have not ratified it have at a point or the other made reference to it. Major economic players apart from England have ratified and have their courts pronounce on the CISG. The Convention provides for the well known elements of contract and also allows for the usage of standard user terms, for example, general terms known or related to certain goods. It is imperial to state that there are also certain regional statutes that are similar to the CISG although with varying differences. It is important to also mention that the CISG also has its lacunae and defects such as allowance for exemption, contents and so on. The CISG has been pronounced upon by courts across the world and has been seen to be highly justiciable.
Keywords: CISG; Convention; English Law; Iraq; United Nations

Affected persons in business rescue proceedings : has a balance been struck? - Silangwe, Thandeka (University of KwaZulu-Natal, 2016)
Abstract not available.
Keywords: Buisness enterprises; Business failures; Corporate turnarounds; South Africa

An analysis of the impact of the sanitary and phytosanitary agreement on market access : case study on the SA/EU citrus dispute and AGOA dispute - Singh, Shikira (University of KwaZulu-Natal, 2016)
Abstract not available.
Keywords: AGOA; African Growth and Opportunity Act; Cooperation Agreement; Market access; Sanitary and Phytosanitary (SPS) Agreement; Trade Development; Trade barrier; WTO; World Trade Organization

The non-cooperative respondent in international arbitration proceedings : a comparative survey and evaluation of the leading arbitration rules - Venter, Johanlene (University of Johannesburg, 2016)
International arbitration has become accepted worldwide as the principal and, under certain circumstances the preferred method, of resolving international disputes between states, individuals, and corporations in almost every aspect of international trade, commerce, and investment. In general terms, it is expected that an international arbitration procedure is a much speedier method of dispute resolution than formal court proceedings. Although international arbitration holds many benefits for prospective users, there are some difficulties that may arise along the way. An increasingly frequent complaint concerns delays, particularly unconscionable delays and deliberate delaying tactics caused by the parties (i.e. claimant, respondent and/or the arbitrator) which frustrates the process. Arbitration derives from the consent between contracting parties. This implies that the contracting parties gave their consent that a dispute arising from the contract may be resolved by way of arbitration. This will also explain why default by any of the parties is prima facie inconsistent with the consensual nature of arbitration. It is suggested that default during international arbitration is most likely to occur and does not receive the same treatment as the equivalent in the context of formal state court proceedings. Essentially, the objective of this study is to articulate what the claimant can and should do during the arbitral process if and when the respondent is non-cooperative and obstructive in the arbitral process in an attempt to delay and/or destroy the procedure. This study also considers how tribunals should behave in order to promote fairness and the most efficient form of dispute resolution. The research method applied during this study is to conduct a comparative survey and evaluation of the leading arbitration rules available in order to establish what measures are put in place to overcome or mitigate the effects caused by the non-cooperative respondent.
Keywords: Commercial law; International commercial arbitration

The suitability of the CISG and OHADA for small and medium-sized enterprises engaging in international trade in West and Central Africa - Donfack, Narcisse Gaetan Zebaze (University of South Africa, 2015)
It is universally acknowledged that international trade and cooperation have become key drivers of SMEs. Indeed, the success of SMEs in the sales sector depends upon their capacity to conquer the foreign market and compete with larger companies. Many SMEs today, in particular those in Central and West Africa, are very much aware of this reality. However, because of differences between domestic laws and their maladjustment, many African SMEs still struggle to enter the international market and compete with larger companies. It is therefore obvious that any SMEs that want to succeed in international commerce today will be called upon to confront different regulations, whether domestic, regional or international, which are often shaped according to the realities and expectations of a particular environment. The challenge today is to regulate and harmonise these different legal systems, in order to render the law identical in numerous jurisdictions. This process of unifying the law internationally, in particular the law of sale, started in 1920 and culminated in 1988, with the implementation of the CISG. This Convention, which has become the primary law for international sales contracts, endeavours to deal with this problem of differences in law between states on a global scale, by attempting to achieve a synthesis between different legislations, such as civil law, common law, socialist law, and the law regarding industrialised and Third World countries. Even though the CISG appears to be a compromise between different legal systems, the fact remains that it is not yet applicable in many countries, especially those in Central and West Africa, which are mostly still ruled by domestic and regional law, namely the OHADA. The purpose of this study is to attempt to analyse and compare the OHADA’s Uniform Act Relating to Commercial Law to the CISG, in order to identify similarities and differences between the two, and to determine, with regard to the operating mode and structure of SMEs in West and Central Africa, which one of the two legislations is more appropriate.
Accepted: 2016-07-19T07:00:06Z
Keywords: CISG; Cameroon Civil Code; Cameroon contract law; Comparative law; Formation of a contract; Incoterms; International sales law; Internationalisation; OHADA law; Obligations of the buyer; Obligations of the seller; SMEs; Sales of goods; Termination of a contract

Passivity rule: a comparison between European Union, United States and China - Casamassima, Stefano (LUISS Guido Carli, 2015)
Passivity rule: origin and reasons. Adoption of the European directive 25/2004 and its provisions. The adoption of the European directive by major member states and passivity rule in USA and China. The economic implications of passivity rule. Possible future developments.

Choice of the UNIDROIT Principles of international commercial contracts - Meer, Tiana Van der (University of Johannesburg, 2015)
LL.M. (International Commercial Law) The principle of party autonomy is a fundamental characteristic of private international law. The contracting parties’ freedom of choice regarding the law governing their contract is one which optimises the fundamental principle of party autonomy. It is generally accepted that a choice of a governing law by the parties should be respected by adjudicating bodies such as domestic courts and arbitral tribunals. It would often benefit contracting parties to choose a neutral legal system so that there will be a “fair playing field” in case a dispute arises between them. However, some domestic legal systems and regional, supranational and international commercial instruments limit the choice of law to that of a recognised domestic legal system. Accordingly, choosing the UNIDROIT Principles on International Commercial Contracts as governing law will, in most cases, not be a viable option for the parties concerned. Such a limitation on the choice of a governing law does not promote the fundamental principle of party autonomy, which is characteristic of private international law. Parties to an international commercial contract should be able to choose a non-state system of law to govern their contract. The UNIDROIT Principles of International Commercial Contracts provide a comprehensive, complete and easily obtainable system of law compiled by legal experts in the various fields which form part of international commercial law. It follows a via media system of law with regards to Civil Law and Common Law legal systems. This paper will discuss the principle of party autonomy, as well as the possibility of a choice of non-state law, in particular the UNIDROIT Principles of International Commercial Contracts, as the law governing an international commercial contract. The choice of law will be discussed with reference to the position taken in domestic courts as well as that in international arbitration. To review the impact and success of the UNIDROIT Principles in the realm of international commercial contracting, various international commercial instruments will be discussed.

The potential impact of the Hague principles on choice of law in international commercial contracts in the BRICS countries - Reddi, Saranya (University of Johannesburg, 2015)
LL.M. (International Commercial Law) Please refer to full text to view abstract
Keywords: BRIC countries; Commercial law; Conflict of laws; Contracts (International law)

A comparison of Kenyan and South African law on security by means of movables - Koli, Natasha Mwende (University of South Africa, 2015)
This study compares the legal principles applicable in both South Africa and Kenya in the creation of security by means of movables. It identifies the forms of security that can be created in the two jurisdictions. The main focus will be on the creation, publicity, priority of security interest and enforcement of the said interests. The research will in addition establish the challenges (if any) that are encountered when creating security by means of movables in Kenya and identify practical solutions that can be adopted in order to improve the creation of security by means of movables in Kenya.
Accepted: 2015-10-16T08:35:59Z
Keywords: ACCESS TO FINANCE; Creation of security; Kenyan law; Lenders and security; Movable property; Secured transactions; Security; Security by means of movables; South African law

Cross border insolvency: new trends - Napolitano, Andrea (LUISS Guido Carli, 2015)
The EU regulation no. 1346/2000. The proposal for a modification of the regulation. New trends.

How to copy a song with impunity : a legal perspective on copyright infringement cases for musical works - Rogowski, Adrian (Stellenbosch University, 2015)
Music has, and continues to play, an important role in society. It is therefore natural that more music composers enter the scene to capitalize upon this role that music has in society. It is however becoming more common place for music composers to start copying each other, either directly or indirectly. Fortunately, copyright laws have been developed to further protect the rights enjoyed by copyright holders, such as music composers, and these laws essentially protect the composers from the unlawful reproduction of their original music. Copying is, to some degree, inevitable, therefore, the question asked by this paper is to what extent is someone entitled to ‘copy’ from another person without it amounting to copyright infringement. In determining if there is copyright infringement, two tests must be applied and satisfied, namely, the causal connection test, and the substantial similarity test. Causal connection is usually met by establishing whether the alleged infringer had access to the original work. The substantial similarity test is the focus of this paper. The courts rely on this test to determine if that part which was reproduced from the original work is of substance i.e. if it is a part of the work which attributes uniqueness and quality to the original song. Of course, this test is notoriously difficult to understand and apply, hence the need for this paper to address the question on when there is substantial similarity in two works. This paper is of benefit to academics, authors (musicians) and lawyers, as not only is the substantial similarity test discussed from a theoretical point of view, but the question of when something is substantially similar is answered from a pragmatic point of view. It is hoped that this paper is used as a guideline in understanding and applying the substantial similarity test in music copyright infringement cases.
Keywords: Copyright; Copyright infringement; Music; Musical compositions

Reconsidering Distributions: A Critical Analysis of the Regulation of Distributions to Shareholders in the Companies Act of 2008, with Special Reference to the Solvency and Liquidity Requirement - Van der Merwe, Constant Pieter (Stellenbosch University, 2015)
The Companies Act 71 of 2008 introduces a completely new system for the regulation of distributions by a company to its shareholders. The preferred method for protecting the interests of creditors in distributions is now based on a solvency and liquidity test. Regrettably, the provisions setting out the requirements for distributions on the one hand and the solvency and liquidity test on the other have been poorly drafted. This thesis first explains and then applies an innovative interpretation theory to these provisions with a view to piecing together coherent content. The thesis finds that creative interpretations will not suffice in various places, meaning that substantive revision is required. The thesis concludes with brief amendment proposals and accompanying commentary.
URI: http://hdl.handle.net/10019.1/97133
Keywords: Business enterprises; Companies; Companies Act; 2008; Companies régulations; Company insolvency; Company liquidity; Insolvency; Régulations; Shareholders; South Africa

The effectiveness of the e-commerce legal framework in selected African countries - Esanwa, Maryam Adetokunbo (University of KwaZulu-Natal, 2015)
Abstract not available.
Keywords: Africa; E-commerce; Electronic commerce; Information technology

A critical appraisal of the misapplications of black economic empowerment and the common misperceptions that surround it - Govender, Prenisha (University of KwaZulu-Natal, 2015)
Broad-Based Black Economic Empowerment is a regulatory framework, which is unique to South Africa. This dissertation reflects upon the evolution of Broad-Based Black Economic Empowerment programme, from the commencement of apartheid to date. Broad-Based Black Economic Empowerment was implemented by government, with the objective of resolving the injustices created by the apartheid regime. Government seeks to achieve this objective by integrating the historically disadvantaged individuals within South Africa into the mainstream of the economy. However, the reality is that the implementation of the Black Economic Empowerment programme has not been entirely successful. This dissertation is a critical analysis of the application of Broad-Based Black Economic Empowerment and related legislation. It aims to highlight the challenges faced by government in enforcing the Broad-Based Black Economic Empowerment programme, with a particular focus on the following issues: fronting, misrepresentations and common misperceptions. This dissertation begins by reflecting upon the historical context of South Africa toward democratization, secondly it analyses the current applicable legislation and explores the current issues. This research shows that Broad-Based Black Economic Empowerment is essentially a work in progress programme as there is much room for improvement. Scholars have established that companies and other entities regularly circumvent the Act. Furthermore, many individuals misunderstand the programme and its purpose. The research concludes Broad-Based Black Economic Empowerment does have potential for success. In considering the approach taken by Malaysia, it is established that the key to overcome these major issues is education.
Keywords: Affirmative action programs; Blacks Economic conditions; Business enterprises; Employee empowerment

Harmonising investment laws in the OHADA space - Mugangu, Marie Providence Ntagulwa (University of Cape Town, 2015)
The Organisation for the Harmonisation of Business Law in Africa (OHADA) was established for the purpose of restoring legal and judicial security in the region to attract more investment. The OHADA Treaty included certain areas of business law within its ambit but omitted investment law. There are several laws on investment in the region at the national, regional and sub-regional level that regulate the treatment of foreign investments such as CEMAC and UEMOA investment charters. Moreover OHADA states sign BITs to protect foreign investments. The relationship between the different sub regional laws on investment and OHADA is not yet clear but case law suggests that CEMAC and UEMOA courts recognise the supremacy of OHADA law and their lack of competence to hear matters regulated under OHADA. The standards of protection granted by OHADA states in BITs are very high thus taxing on them. This thesis suggests that OHADA states should either qualify these standards of protection or replace them with more specific provisions. The OHADA system of arbitration cannot effectively settle investment disputes arising out of a BIT leaving international arbitration systems such as ICSID as the best alternative to resolve investment disputes arising out of BITs.
Keywords: International Trade; International Trade Law; Investments

Avoidance of a contract under the CISG - Otenga, Emongo Jean-Marc (University of Johannesburg, 2015)
Keywords: CISG; Commercial law; Contracts (International law); United Nations Convention on Contracts for the International Sale of Goods (1980 April 11)

A comment on debt relief options for insolvent consumer debtors in South Africa - Xulu, Anele Innocentia Nombuso (University of KwaZulu-Natal, 2015)
The paper will be focused on examining the debt relief options available for consumer debtors in South Africa. This paper will look at the relationship between the National Credit Act 34 of 2005 and the Insolvency Act 24 of 1936. Further, it will examine the relationship between the provisions of section 74 of the Magistrates’ Courts Act 32 of 1944. The paper will conclude by looking at debt relief options available for consumer debtors in the United States of America and in England and Wales and will make comparative comments and recommendations on how we can adopt some provisions into our own insolvency system.
Keywords: Consumer credit; Debt relief; Debtor and creditor; Insolvency; Insolvency Act; National Credit Act; South Africa

The transfer of movables in the international commercial context – a comparison of German and South African law - Lengyel, Martin (University of Johannesburg, 2014)
L.LM. (International Commercial Law) Please refer to full text to view abstract
Keywords: Contracts (International law); Germany; International Commercial Law; Law of property; Property; South Africa

Proposal for a regulation on a common European sales law - Ciceri, Eliane (LUISS Guido Carli, 2014)
Historical development. Five W of CESL. Common European sales law.

The strategic importance of regional economic integration to multinational companies (MNCs) : a study of South African MNCs' operations in the SADC - Egu, Mathew Eleojo (University of South Africa, 2014)
Though the strategic importance of regional economic integration to multinational companies (MNC) has been researched extensively internationally, this concept has not been studied in South Africa. In fact, there is a growing nostalgia that with the South African Development Community (SADC) moving towards its set macroeconomic convergence targets; regional economic integration eventually leads to macroeconomic stabilisation. This ultimately becomes the root of growth in a region that has been severely affected by globalisation, financial crises, increasing government debt and budget deficit problems. This study, hence, tries to find out how the critical decisions of South African MNCs are made when operating within regional markets. Consequently, statistical econometric models were developed to test time-series data from 1980-2011 using the best (most efficient) linear unbiased estimator (BLUE) ordinary least square regression technique. An analysis was then done to investigate how South African firms have been able to gain maximum benefits by adopting the SADC as its major trading bloc in Africa. The study’s findings showed that the major barriers that impede MNCs of South African origin from penetrating these markets were custom duties, direct and indirect tariffs. It was observed that this would only be reduced by regional integration. Determined to critically interrogate the problems detailed in this research, three hypotheses were tested, analysed and subsequent interpretation of the findings revealed that South African MNCs contribute positively to regional economic growth and investment in the SADC. Furthermore, the study found out that although these factors were important, they were not the only variables that stimulated the competitiveness of South African MNCs in the SADC region. The literature review sections of this study found that the adoption of strategic management initiatives by MNCs improved the operation of transnational companies in South Africa. A comparison between the value of South African MNCs, as well as, other explanatory variables, and the Gross Domestic Product (GDP) of both South Africa and the SADC using time series data for the period 1980-2011 indicated that there was a positive relationship between the contribution of MNCs to South Africa’s economy and the GDP of both South Africa and the SADC. This proved that there is a significant link between MNC growth and national/regional productivity. In conclusion, the study established that the findings of the literature review were theoretically in sync with the empirical analysis. Also, the outcome of this study concurred with the findings of similar research. In essence, regional trade arrangements are an increasingly important element of the global trade environment, of which the move by South Africa’s MNCs to operate in the SADC market was a positive one. Finally, the study found out that for these firms to be successful in the international business arena, business management decisions need to be made, only after a detailed strategic analysis of the significance of regional economic integration is considered. This integrative framework certainly determines the operational efficiency, survival and profitability of most MNCs that operate within the region.
Accepted: 2014-10-01T07:01:54Z
Keywords: FDI; Foreign direct investment; Macroeconomic convergence; Macroeconomic stability; Mergers & acquisitions; Multinational companies; Regional Economic Community; Regional Trade Agreements (RTAs); SADC; South Africa Development Community; Strategic management

The compatibility of Australian and South African private international law with the Hague Principles on Choice of Law in International Commercial Contracts - Adams, Faadhil (University of Johannesburg, 2014)
In 2006 the governing body of the Hague Conference on Private International Law furnished the Secretariat with a mandate to conduct a series of feasibility studies on the development of an instrument, relating to the choice of law in international contracts. The outcome of these studies was largely successful, finding that there was a need for an instrument of this nature and additionally it would be welcomed by the international legal community. In 2009 the Permanent Bureau of the Hague Conference on Private International Law was invited to form a Working Group (WG) to draft a soft-law instrument affirming party autonomy in international contracts on an international level. The Hague Principles on Choice of Law in International Commercial Contracts (P) was, thus, born. The P were drafted by a panel of experts representing the majority of the world’s legal systems. The working group commentary (WGC will be used to refer to the commentary, whilst WG will be used to refer to refer to the working group itself) which provided the discussions in respect of, and the reasoning behind, the principles has been invaluable in writing this dissertation. The purpose of this dissertation is to investigate the compatibility of Australian and South African law with the P. One of the aims of the P mentioned specifically in the preamble is that these principles are to be used by countries as a model with which to develop their own rules of private international law. A study of the current law as it stands in comparison to the P marks the first step in this exercise, through finding where the law differs we can begin to bridge the disparity between a specific country’s legal system and that of the P. Should the P become an important part of the private international law discourse comparative studies such as this will become common-place. The fact that the principles were drafted as a soft-law instrument is in line with the growing world trend. The flexibility that is achieved through the use of a soft-law instrument may lead to greater legal certainty down the road as contracting parties and international lawyers alike become more familiar with the principles. This familiarity may lead to consensus among experts from around the world and eventually invite the prospect of a binding instrument being drafted
Keywords: Australia; Conflict of laws; Contracts; Contracts (International law); South Africa

Addressing the legal issues of an innovative start-up company - Samoylov, Vlad (Victoria University of Wellington, 2014)
Before examining the substance of the law it is necessary to discuss the contrast between law and practice. It is important to keep in mind that the letter of the law is sometimes not what is done in practice. This realisation is often referred to as the “law and society perspective.” Advocates of this perspective treat legal doctrine as more than just a closed system because they recognise that there are other external influences at play. Beyond the law, people are also influenced by other factors such as social roles, morals, religion and culture. For example, university researchers have an external incentive mechanism outside of IP law. Such researchers frequently prefer to publish their results and discoveries in academic journals rather than file for patents. A patent cannot be granted where there has been a publication. However the researchers are motivated by other incentives such as access to research funds and the attainment of professorship. The Law and Society perspective highlights the fact that the formal processes, which are provided for by the law are at times substituted by informal customs and understandings. An information technology (IT) firm that contributed to this paper by participating in an interview (Interviewee A), provided a good example of such an occurrence. Rather than use any of the formal IP modes of protection which are discussed in the following sections of this paper, ‘Interviewee A’ uses a very unorthodox strategy to protect their IP. They said: “we rely on employment contracts, code of conduct, and especially personal ethics and behaviour to protect our IP. We therefore have a company culture that encourages teamwork and cooperation”.
Keywords: Intellectual property; Product safety standards

Mediation advocacy - Shaw, Annabel (Victoria University of Wellington, 2014)
Mediation has been a part of New Zealand’s employment statutory framework in one form or another for over a century, and has been the first port of call for employment disputes under the current Employment Relations Act for nearly 15 years.¹ I have been working as a mediator in this context for almost seven years in more than 1,000 mediations. Lawyers are playing a significant part in the field of mediation, with a large number representing clients in this forum on a regular basis. In an evaluation of 100 of my mediations over a ten-month period, 85% of parties were legally represented. This rate is consistent with anecdotal reporting across the employment mediation service. Lawyer representation in mediation is not unique to the employment context. There are various mediation schemes provided for under many New Zealand statutes as well as a wide raft of non-statutory mediation occurring in numerous settings. In my experience as a mediator with human rights and leaky building mediations, as well as working as a lawyer in a large commercial law firm, I am aware lawyers are representing clients in many other areas of mediation as well. Although there is a significant amount of mediation occurring and a large number of lawyers regularly appearing in mediation, my experience is that the majority of lawyers act in mediation as if they were in litigation and take an adversarial approach. My thesis is that lawyers have not adapted effectively to mediation and taken on the role of mediation advocacy. This paper explores the topic by first describing, in Part II, what I observe as lawyers’ adversarial approach in mediation. It then looks at other research to assess whether this experience is reflective of a wider issue. It finds there is evidence to support my observations. Part III analyses why lawyers are operating in an adversarial way in mediation and proposes several reasons this may be the case. Part IV puts forward what I propose is appropriate mediation advocacy. It sets out the knowledge, roles and skills required from lawyers when representing clients in mediation. Part V suggests what might be done to assist a shift away from the common, adversarial approach to effective mediation advocacy. This paper is written within the context of employment mediation in New Zealand. However, it draws on research from different jurisdictions and areas of practice so the conclusions it comes to may have more general application. The topic is not whether lawyers should be in mediation. I am not arguing that lawyers do not have a part to play in mediation. A lawyer well versed in mediation advocacy can play a highly effective part in the process. Leonard Riskin, one of the key authors on the topic of lawyers in mediation, expresses this even more strongly, saying he believes lawyers’ involvement is fundamental to mediation’s success.² Further, this paper is focused on lawyers representing parties in mediation and does not consider lawyers as mediators.
Keywords: Advocacy; Dispute resolution; Employment disputes; Lawyers; Mediation

Sanitary and phytosanitary measures in the SADC region : a South African legal perspective - Joubert, Biandri (North-West University, 2014)
Sanitary and phytosanitary (SPS) measures are measures aimed at the protection of human, animal and plant life and health within specified territories from the risks associated with the introduction and spread of pests and diseases through trade. The World Trade Organisation (WTO) developed an agreement on the application of SPS measures. South Africa is a member of both the WTO and the Southern African Development Community (SADC). In SADC, SPS measures are provided for in the SADC Sanitary and Phytosanitary Annexure to the Protocol on Trade of 1996. International Standard Setting Bodies (ISSBs) facilitate the effective application of the main elements of the relevant SPS agreements, especially harmonization and equivalence by establishing scientifically justified standards on which members may base their SPS measures. The relevant ISSB’s in terms of SPS measures are the OIE, IPPC and Codex Alimentarius. SPS measures have the potential to become or be used as non-tariff barriers to trade (NTBs). The SADC Protocol on Trade 1996 stipulates that policies and measures are to be implemented by members to eliminate existing forms of NTBs. Additionally members may not enforce new NTBs affecting or related to intra-SADC trade. The most relevant South African legislation in the context of SPS measures and this study is as follows: Agricultural Pests Act 36 of 1983, the Agricultural Products Act 119 of 1990; the Fertilizers, Farm Feeds, Agricultural Remedies and Stock Remedies Act 36 of 1947, the Liquor Products Act 60 of 1989, Meat Safety Act 40 of 2000, Foodstuffs, Cosmetics and Disinfectants Act 54 of 1972, Medicines and Related Substances Act 101 of 1965 and National Regulator for Compulsory Specifications Act 5 of 2008. The purpose of this study is to establish to what extent the South African legal framework complies with its obligations in terms of the SADC SPS Annexure to the Protocol on Trade.
Keywords: ISSB; NTB; SADC; SPS; Sanitary and phytosanitary measures; South Africa; WTO

A critical assessment of the impact of SPS measures on market access for developing countries : case study of South Africa and Kenya - Mupure, Ngonidzashe L. A. (University of KwaZulu-Natal, 2014)
Abstract not available.
Keywords: Developing countries; Economic conditions; Economic development; International Trade; Kenya; Phytosanitation; South Africa

A critical discussion on foreign direct investment in the multilateral trade system and development in SADC - Nhlakanipho, Macmillan Zikalala (University of KwaZulu-Natal, 2014)
Development is understood to be an economic process that aims at a constant improvement of the well-being of all individuals who have the right to participate and benefits from the fruits of development. Development is also a right that requires a progressive realisation by governments, international communities and private sectors to the satisfaction of all individuals. A progressive realisation of this right requires a vibrant economy, which can be acquired through International trade and Foreign Direct Investment (FDI). It is in this context that this thesis has attempted to discuss the influence of FDI and International trade on development. The discussion was initiated by focusing on the history of the multilateral trade system (MTS) by looking at various Ministerial rounds of both the General Agreement on Tariffs and Trade (GATT) and the World Trade Organisation (WTO). In this discussion the thesis found that, whilst there are various multilateral political frameworks regulating trade, FDI is subject to regional and domestic political frameworks. The thesis also discussed development in relation to the millennium development goals (MGDs). It was established the goal eight of the MDGs requires the integration of poor countries into the MTS so that they can be able to exploit their comparative advantage. This goal influenced the launching of the Doha Development Agenda (DDA) at the Doha round in 2001. However, the thesis also established that conclusion of the DDA has been progressing at a slow pace. Therefore it has not yielded substantial results for poor countries. The failure to conclude the DDA has led to an increase of Regional Trade Agreements (RTAs), which some scholars view as a supplement of multilateral trade integration. However, the SADC region has not been able to conclude their integration objectives due to the fact that many member states belong to other RTAs. In the case of FDI the thesis established that FDI is accompanied by a wide range of resources for host countries, which can be utilised for enhancing development. However, it was also established that the SADC has not been able to attract lucrative FDI due to a wide range of factors that impede FDI. On this finding, a case study was employed on four countries in the region, namely Angola, Botswana, South Africa and Zimbabwe.
Keywords: Economic Policy; FDI; Foreign direct investment; International Trade; International economic relations; Investments

Copyright and developing countries a critical examination of recent developments in copyright law with particular reference to the impact on developing countries and access to educational materials - Siphepho, Nomvuyo Nicole (University of KwaZulu-Natal, 2014)
Abstract not available.
Keywords: Copying processes; Copyright; Developing countries; Instructional materials industry

Corporate governance in Kenya's state corporations: A critique on the appointment and dismissal of directors of boards of state corporations - Kamau, A. G. N. (University of Nairobi, 2013)
This study interrogates corporate governance practices within Kenya’s State Corporations with particular reference to the appointment and dismissal of directors of the Boards of these corporations. It recognizes that these directors are the anchors for the implementation of corporate governance practices in these corporations. The appointment and dismissal of these directors have been based on, inter alia, political considerations kinship, patronage, ethnicity and other non objective criteria other than merit. This has often impacted negatively on the performance of these corporations. This study traces the evolution of corporate governance generally, documents it’s historical development in Kenya and examines the current practices on the appointment and dismissal of directors of boards of state corporations. The data collected targeted a majority of State Corporations which demonstrates that past criteria for Directors recruitment and their dismissal was based on non objective criteria. The study is instructive on the fact that though best practice and corporate governance principles have not been fully embraced in the appointment and dismissal of Directors of Boards of State Corporations there is a positive move towards the adoption of these principles in such appointments and dismissals. The impetus for this was the promulgation of the Kenya constitution 2010 which is itself a good corporate governance document.

Business income and passive income in the UN model double taxation convention - Mascia, Susanna (LUISS Guido Carli, 2013)
The historical evolution of the UN model convention. The UN model convention’s subjective and objective scope. The determination of active income: current points of difference between the UN and OECD models. The determination of passive income: differences and similarities between the UN and the OECD model conventions. Transfer pricing.

Unlocking Africa's poverty trap : holistic approach to BOP investment in agribusiness - Suzuki, Elli (Massachusetts Institute of Technology, 2013)
This paper identifies subsistence farming as a significant opportunity for poverty reduction and economic development in sub-Saharan Africa. By taking a holistic, standardized, and bundled approach, this paper proposes an innovative business model that enables small-holder farmers to access affordable extension services, technical assistance and financial scheme, thereby improving their overall productivity level.

A Comparative study of some issues relating to Corporate Insolvency Law in Nigeria and South Africa - Habi, Halita Mafo (University of Pretoria, 2013)
No abstract available

Users' entitlements under the fair dealing exceptions to copyright - Shay, Richard Michael (Stellenbosch University, 2012)
This thesis analyses current South African copyright law to ascertain the proper interpretation and application of the fair dealing provisions contained in the Copyright Act 98 of 1978. Copyright law ensures that authors’ works are not used without their consent, which they can grant subject to compensation or conditions attached to the use. Fair dealing exceptions allow the general public to use copyright works for certain purposes without the copyright owner’s consent and without paying compensation. These provisions are intended to balance copyright owners’ interests with the interest that members of the public have in using copyright works for socially beneficial purposes. These provisions typically allow the use of a copyright work for the purposes of research or private study, personal or private use, criticism and review, and news reporting. Unfortunately there is no South African case law concerning the fair dealing provisions, and the application of these exceptions remains unclear. This study aims to clarify the extent of application of the fair dealing exceptions to copyright infringement so that courts may be more willing to consider foreign and international law and in doing so develop South African intellectual property law. The social and economic policy considerations underlying the fair dealing exceptions are considered to determine their function. International conventions relating to copyright and neighbouring rights are examined, specifically the provisions allowing exceptions to copyright. The legislation and case law of Australia and the United Kingdom are analysed to determine the proper interpretation and application of these statutory defences. This knowledge is then used to inform South African law. The Copyright Act 98 of 1978 does not contain a fair dealing exception for parody and satire. Australian legislation does contain such an exception, and it is analysed in that context. An exception for parody is proposed for South African law, and the need for and application of this provision is considered. The constitutionality of the proposed exception is evaluated in terms of its impact on the constitutional property rights of copyright owners.
Keywords: Australia; Copyright law; Fair dealing; Fair use; Great Britain; Intellectual property; South Africa; Trademarks

The Influence of ICC Arbitral Decisions on Canadian Law: Comparative Study between Civil Law and Common Law Jurisdictions - Hedaraly, Saleha (Université de Montréal, 2012)
L’objectif de cette recherche est de démontrer que les décisions arbitrales de la Chambre de commerce internationale peuvent être considérées comme une source potentielle de droit au Canada. Il existe actuellement une incertitude quant au droit matériel utilisé en arbitrage international pour résoudre les différends commerciaux. Bien que l’utilisation de la lex mercatoria pour résoudre un litige soit une option, elle se heurte à de nombreuses incertitudes terminologiques et conceptuelles. L’utilisation d’une approche méthodologique de la lex mercatoria permettrait une classification de ses sources en deux branches: (1) le droit statutaire international et (2) le stare decisis des tribunaux d’arbitrage commercial international. Une telle approche méthodologique conférerait plus de certitude quant à l’application d’un droit uniforme. De plus, elle faciliterait l’étude de l’interlégalité entre les règles de la lex mercatoria et le droit matériel interne. Plus particulièrement, elle permet de comparer les similitudes et les différences des règles du droit matériel entre les décisions arbitrales internationales, le droit statutaire international et les juridictions canadiennes de common law et de droit civil. Cette comparaison rend possible une évaluation de l’influence potentielle des décisions arbitrales de la Chambre de commerce internationale sur le droit matériel canadien et si cette influence est plus importante en droit civil ou en common law. This paper’s objective is to demonstrate that the International Chamber of Commerce’s arbitral awards may be considered as a potential source of law in Canada. There currently exists an uncertainty as to the substantive law used in international commercial arbitration. While the use of lex mercatoria to solve commercial disputes is often referred to, several terminological and conceptual uncertainties undermine its credibility. The use of a methodological approach to lex mercatoria allows for a twofold classification of its sources through: (1) international legislation and (2) stare decisis from international arbitral tribunals. This methodological approach provides a greater certainty for the application of a uniform law which, in turn, allows for the study of interlegality between rules of lex mercatoria and substantive domestic law. Furthermore, this methodological approach facilitates the demonstration of the similarities and differences between international arbitral decisions, international legislation as well as Canadian common law and civil law jurisdictions. This comparative analysis will allow the study of the potential influence of the arbitral decisions of the International Chamber of Commerce on substantive Canadian law and whether this influence is more important in civil law or common law.
https://papyrus.bib.umontreal.ca/xmlui/bitstream/handle/1866/12719/Hedaraly_Saleha_2012_memoire.pdf
Keywords: Approche méthodologique; Arbitrage; Arbitragem; Arbitral decisions; Arbitration; CCI; Civil law; Common law; Droit civil; Droit commercial transnational; Décisions arbitrales; ICC; Interlegality; Interlégalité; Lex mercatoria; Methodological approach; Sentences arbitrales; Transnational commercial law

A regulatory framework for the trans–boundary transportation of dangerous goods in Southern Africa : an environmental perspective - Ashukem, Jean-Claude Nkwanyuo (North-West University, 2012)
The goal of this dissertation is to analyse the extent to which the South African legal framework governing the trans-boundary transportation of dangerous goods, provides for the regulation of environmental aspects in terms of dangerous goods transportation. The dissertation examines the role of regional and sub-regional laws in this regard in an effort to ascertain whether there is sufficient legal certainty and harmonisation of laws for environmental regulation. No specific law currently exists in South Africa regarding the regulation of dangerous goods transportation, rather the regulation of dangerous goods is effected by a multiplicity of laws. This state of affairs illustrates the difficulty that exists and may be associated with the enforcement of the regulation of dangerous goods transportation. Despite this, the multiple laws vividly elucidate the fact that there is a considerable degree of environmental protection vis-a-vis dangerous goods transportation premised on the fact that all environmental impacts could never be avoided or eliminated, but can be reduced to an extent.

Combating insider trading in Kenya's capital markets: challenges and opportunities for reform - Kotonya, Anne (University of Nairobi, 2012)
The capital markets are expected to play a pivotal role in the attainment of Kenya's development blueprint 'vision 2030.' It is, therefore, essential that obstacles to the attainment of a fair and efficient market are examined and rooted out. This study investigates the limitations of the Capital Markets Act in combating insider trading. It also examines whether reforms would promote a fair and efficient capital market. The study makes use of existing literature as well as decided cases to investigate the inadequacies in the formulation of and provisions for inside information, material pricesensitive information, publication of information, possession of information and disclosure of information in the Capital Markets Act. This literature draws out key learnings from other jurisdictions and analyses how legislation in developed economies treats challenges to the enforcement of insider trading laws. The doctrinal analysis is triangulated with results of a survey of practical experiences of legal practitioners in applying the Capital Markets Act. The findings affirm the existence of conceptual difficulties in determining the elements of the crime of insider trading. As a consequence, it is concluded that the present formulation of insider trading law is inadequate. The study, therefore, makes suggestions for reforms to the provisions on insider trading in the Capital Markets Act.

Challenges to regional intergration in the SADC region : a legal perspective - Mwanawina, Ilyayambwa (North-West University, 2011)
The Southern African Development Community (SADC), formerly known as the Southern African Development Coordination Conference (SADCC), is an organization of Southern African states initially formed to reduce economic dependence on South Africa (then an Apartheid state) and to harmonize and coordinate development in the region. The vision and mission of SADC reach well beyond the harmonization of development within the region. It extends to fields that include political stability, peace building, the maintenance of security and justice as well as economic cooperation. The attainment of these goals requires well co-ordinated regional mechanisms; as such over the past decade member states have paid particular attention to the possibility of attaining these goals through regional integration. The transformation from SADCC to SADC indicated that the body would no longer be a loose association (conference) of states but rather a regional body that would have a legally binding effect on its member states. The question is, when the member states assembled in Windhoek, August 1992, did they create an institutional framework, and policies that would have enough legal force to ensure that the institutional agenda of integration is not defeated by member states? The argument of this dissertation is that the Treaty and the policies established afterwards contain principle imperfections that are self defeating for the pursuance of regional integration. The work will begin by discussing regional integration in general, highlighting the historical origins of SADC as well as the role of the African Union. The work will then discuss the dimensions and functioning of SADC, laying the foundation for a proper critique on how the institutional framework contains inherent weaknesses that eventually hinder the progression of SADC. The dissertation ultimately will discuss and benchmark the European Union against SADC, in an attempt to extract important lessons for the progression of SADC.
Accepted: 2016-01-10T22:52:56Z https://repository.nwu.ac.za/handle/10394/15788
Keywords: Africa; Interregionalism; Southern

International convention for the control and management of ships' ballast water and sediments, 2004 - Robe Hughes, Charlotte (Aix-Marseille Université, 2011)
Will harmonization of legislation relating to the management of ships’ ballast water be achieved, once IMOs’ 2004 Convention enters into force?

Legal origins, legal institutions and poverty in Sub-Saharan Africa - Baldelli, Federico (LUISS Guido Carli, 2010)
The traditional and religious layer. The colonial layer. Law of independence. Law in Sub-Saharan Africa today. Common law and civil law in Sub-Saharan Africa. The consequences of legal origins. Legal origins and legal institutions in Sub-Saharan Africa. Legal origins and poverty in Sub-Saharan Africa. An econometric model.